Laparoscopic Sacropexy: A Retrospective Analysis of the Subjective Outcome in 310 Cases. (7th September 2011) - Bojahr, B.; Tchartchian, G.; Waldschmidt, M.; Ohlinger, R.; De Wilde, R. L.
Abstract : Background and Objective . The aim of this study was to assess the subjective outcome following laparoscopic sacropexy. Methods . We performed a retrospective cohort study among women treated for descensus with laparoscopic sacropexy between January 2000 and December 2007. 310 patients received questionnaires during followup assessing major pre- and postoperative symptoms and overall satisfaction. Results . 214 (69%) patients responded to the questionnaire. Mean followup was 24.5 months. The number of patients with back or lower abdominal pain, foreign body sensation in the vagina and prolapse-related symptoms, urinary symptoms, vaginal and bladder infections, and the need for pessary usage decreased significantly postsurgically. Bowel symptoms increased slightly but not significantly. Two years after surgery, nearly 2 thirds of the women were satisfied or very satisfied with the outcome. Conclusion . Laparoscopic sacropexy is an effective treatment of descensus, with favorable or satisfactory subjective outcomes.